2012
DOI: 10.1089/aid.2011.0117
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Similarity Analysis of HTLV-1 Isolates from HIV-Coinfected Patients from the South and Southeast Regions of Brazil

Abstract: BackgroundHTLV-1 is endemic in Brazil (0.07-15.9%) and HIV/ HTLV-1-coinfection has been detected, mostly in the North and Northeast regions. This study characterized HTLV-1 isolates from HIV-coinfected patients from Southern and Southeastern Brazil. Material and methodsDNA from 17 HIV/HTLV-1-co-infected patients; 5 from the South and 12 from Southeast were amplified by nested-PCR (env and LTR) and sequenced. HTLV subtyping was performed by NCBI-Genotyping and REGASubtyping tools websites and by phylogenetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
4
16
0
2
Order By: Relevance
“…HTLV-1aA is the major circulating viral subtype in Brazil, and the states of Bahia [40], São Paulo [41] and Pará [42] have the highest prevalence rates of infection. Analyses conducted in HTLV-1 carriers in Brazil, both symptomatic (TSP/HAM) and asymptomatic, indicated that the prevalence of HTLV-1aA was greater than that of other viral subtypes and subgroups [43].…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1aA is the major circulating viral subtype in Brazil, and the states of Bahia [40], São Paulo [41] and Pará [42] have the highest prevalence rates of infection. Analyses conducted in HTLV-1 carriers in Brazil, both symptomatic (TSP/HAM) and asymptomatic, indicated that the prevalence of HTLV-1aA was greater than that of other viral subtypes and subgroups [43].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] To gain further insight into the history of HTLV-1 in Brazil, especially in the at-risk population infected by HIV-1 in the south and southeast regions, we conducted the present and preliminary studies. A few years ago, we determined the prevalence of HTLV-1 and HTLV-2 in patients with HIV/ AIDS from Londrina and its vicinities in the south of Brazil and detected HIV/HTLV-1/2 coinfection in 6.4% of cases 16 ; subsequently, we characterized HTLV-1 isolates from southern and southeastern Brazil using the LTR and env regions 17 and confirmed the HTLV-1a Cosmopolitan subtype, subgroup A, which clustered into two Latin American clusters.…”
mentioning
confidence: 99%
“…The study population consisted of 13 patients with HIV/AIDS who were coinfected with HTLV-1 from Londrina and its vicinities (BRLO) and Sã o Paulo (BRSP). 17 Five patients are from Londrina (five men) and eight are from Sã o Paulo (five women and three men). DNA samples were extracted from peripheral blood leukocytes, and the tax region was amplified using a previously described modified protocol, 11 in which PCR was optimized using the GoTaq Colorless Master Mix (Promega Corporation, Madison, WI) to improve stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In October 2012, using PCR protocols optimized for Brazilian isolates, [13][14][15] we retested the patient's blood sample from 2002 and compared it with a new blood sample from 2012; both samples were positive by PCR for HTLV-1 and …”
Section: 12mentioning
confidence: 99%